Meaning and Life-plan Program: Guidance for Adults 50 Years of Age and Older - Rivière, Bernard; Gueddar, Laure (Canadian Journal of Counselling and Psychotherapy, 2013)
This article is based on the results of a meaning and life-plan program, which uses an autobiographical methodology. The analysis is based on the midlife narratives of adults (n =78). The study highlights the following themes: the actual process experienced by the participants, group support, and the emergence of a meaningful plan for the future.